Hubungan Sikap Dan Perilaku Dengan Tingkat Pengetahuan Terhadap Pencegahan Infeksi Covid-19 - Alim Shafiyyur; Fathee Karim (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
At the beginning of 2020, the world was shocked by the outbreak of a new variant of the virus, namely coronavirus (SARS-CoV-2) and the disease was called Coronavirus Disease (COVID-19). It is known that this virus originated in Wuhan, China at the end of December 2019. To date, it has been confirmed that hundreds of countries have been infected with this virus. . Covid-19 is a group of viruses that can infect the respiratory system. In many cases, this virus causes mild respiratory infections, such as flu. However, this virus also causes severe respiratory infections, such as lung infections (pneumonia). WHO itself has declared Corona Virus Disease 2019 (COVID-19) a pandemic, as well as the Indonesian Government based on Presidential Decree Number 11 of 2020 concerning Determining a Public Health Emergency Corona Virus Disease 2019 (COVID-19) has declared COVID-19 an emergency public health that must be taken to overcome. This pandemic condition has had a broad impact on various sectors, starting from the economic sector, tourism, and so on. Many activities have been affected and can even be said to have been hampered due to the Corona outbreak.